University-business cooperation in Kazakhstan: influencing factors (Journal of Economic Research & Business Administration, 2020)
The importance of collaboration between universities and business (UBC) continues to grow in allcountries. The reasons for this are numerous, such as changes in innovation structures, the developmentof the knowledge society, and national and international higher education policies. Kazakhstan,as a rapidly developing country, is experiencing all these changes. Nowadays, activities of universityare evolving from the basic functions of teaching and research to commercialisation of research resultswhere the partnership with the private sector is one of the most important elements. The purpose of thearticle is to identify influencing factors, driving factors and barriers for UBC, as well as recommendationsfor the future. The data for analysis was obtained using an online survey. The survey was conductedamong University employees and company employees. More than 100 respondents took part in thesurvey. The results of the survey show that the main factors influencing the cooperation of universitiesand business: sources of funding, innovative indicators of universities, the impact of funding sources oncontrol mechanisms and innovative activities of universities, also, the likely reason for the lag is the slowand still incomplete transition of Kazakhstan from the “traditional” innovation system to the modern innovationecosystem.